Peru : Third Review Under the Stand-By Arrangement and Request for Establishment of Performance Criteria and Waiver of Applicability. (IMF Staff Country Reports; Country Report ;, 2006)
The staff report for the Third Review under the Stand-By Arrangement and request for establishment of performance criteria focuses on Peru's economic developments, outlook, and program for 2006. The Peruvian economy continues to perform well. Fiscal transparency has been increased, including by establishing a reporting system of public sector liabilities associated with private-public-partnership (PPP) operations. Although the government has so far preserved a consensus for prudent policies and reform, some volatility has recently developed in the stock and foreign exchange markets as the election campaign gains momentum.